Exploring the Synergistic Effect of Curcumin on Gelatin Films for Real-Time Pork Freshness Assessment - Adu, Risna Erni Yati; Gelyaman, Gebhardus Djugian; Kia, Kristoforus Wilson; Oki, Emirensiana; Silab, Maria Desi; Knaofmone, Angelina (Chimica et Natura Acta, 2025)
A smart film based on hydromethanol-curcumin has been developed as a freshness detector for local packaged pork. It was fabricated using solution casting method by varying the curcumin content to determine its effect on the chemical, physical, mechanical and functional characteristics of the film. Film characteristics were determined using colorimeter, TGA, FTIR, SEM and bioactivity assay. Film response was analyzed in different pH buffer solutions, different acid base media and pork samples during the storage period. Film characteristics such as antioxidant, antibacterial activity and surface color was improved by increasing curcumin concentration. On the other hand, mechanical dan physicochemical characteristics such as tensile strength, water content, swelling index and water solubility decreased along with increasing curcumin concentration. Curcumin concentration have no significant effect on the thermal stability and color brightness of the film. SEM images show that increasing curcumin concentration results in aggregation of the gelatin biopolymer matrix. Gelatin-curcumin film was sensitive to pH changes either in gas or liquid media. The properties of the proposed film have high potential to be used as a freshness detector for local packaged pork.